2021
DOI: 10.2147/cmar.s293322
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA NOP14-AS1 Promotes Tongue Squamous Cell Carcinoma Progression by Targeting MicroRNA-665/HMGB3 Axis

Abstract: Purpose The expression profile, clinical effects, and detailed roles of NOP14 antisense RNA 1 (NOP14-AS1) in tongue squamous cell carcinoma (TSCC) remain ambiguous and need to be further explored. Thus, this work was initiated to offer further solid evidence regarding the expression and roles of NOP14-AS1 in TSCC. Furthermore, additional efforts were exerted to reveal the molecular events by which NOP14-AS1 affects the malignant behaviours of TSCC. Methods NOP14-AS1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…HMGB3, from the high-mobility group box subfamily, participates in the cell proliferation, metastasis, and apoptosis in cancers ( 18 , 22 ). Consistent with results of the previous studies ( 20 , 30 , 31 ), we found that HMGB3 was upregulated in EOC tissues and cells. In vivo experiments further confirmed that HMGB3 knockdown diminished the tumor volume and reduced the protein level of Ki-67 in mice.…”
Section: Discussionsupporting
confidence: 93%
“…HMGB3, from the high-mobility group box subfamily, participates in the cell proliferation, metastasis, and apoptosis in cancers ( 18 , 22 ). Consistent with results of the previous studies ( 20 , 30 , 31 ), we found that HMGB3 was upregulated in EOC tissues and cells. In vivo experiments further confirmed that HMGB3 knockdown diminished the tumor volume and reduced the protein level of Ki-67 in mice.…”
Section: Discussionsupporting
confidence: 93%
“…Functionally, NOP14‐AS1 depletion promotes apoptosis and impedes cell proliferation, migration, and invasion in TSCC. 33 Zhang et al 34 reported that LINC01564 suppresses the inhibitory impact of miR‐107/103a‐3p on phosphoglycerate dehydrogenase gene expression, increasing HCC development. Furthermore, Ke et al discovered that elevated LINC01564 expression is linked to a worse prognosis in patients with testicular cancer.…”
Section: Discussionmentioning
confidence: 99%
“…High NOP14‐AS1 expression is associated with poor prognosis in TSCC patients. Functionally, NOP14‐AS1 depletion promotes apoptosis and impedes cell proliferation, migration, and invasion in TSCC 33 . Zhang et al 34 reported that LINC01564 suppresses the inhibitory impact of miR‐107/103a‐3p on phosphoglycerate dehydrogenase gene expression, increasing HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…A common experimental strategy identifies a differentially expressed antisense transcript in cancer vs. untransformed cells followed by miRNA target gene prediction and experimental validation [14], ideally demonstrating the direct interaction between miRNA and target antisense transcript [47]. Alternatively, immunoprecipitation of Ago2 followed by RT-qPCR was used to corroborate the interaction between the miRNA and its target antisense transcript [48].…”
Section: Discussionmentioning
confidence: 99%